Refractive index of dye solution - Mat Yunus, Wan Mahmood (Optical Society of America, 1989)
This Letter reports the variation of the refractive index of rhodamine 6G in methanol for a concentration range of 5 × 10−6–10−4 M at 0.6328-μm wavelength.